Validity of Velocity Measurements of a Motorized Resistance Device During Change of Direction - Eriksrud, Ola; Ahlbeck, Fredrik; Harper, Damian; Gløersen, Øyvind (Frontiers in Physiology, 2022)
The aim of this study was to determine validity of velocity measurements of a motorized resistance device (MRD) during change of direction (CoD). Eight male (age: 22.1±4.2 yrs; weight: 83.3±17.1 kg; height: 181.6±12.6 cm) and three female participants (age: 21.7±1.5 yrs; mass: 69.7±2.4 kg; height: 167.0±3.6 cm) completed the modified 505 CoD test (m505) with turning off the left and right foot while exposed to external loads (3, 6 and 9 kg) provided by the MRD. Three-dimensional kinematic data was measured (200 Hz) for all tests using a full-body marker set with an additional marker placed on the pulley used to attach the carabiner (CAR) at the end of the line from the MRD to the participant. Average velocity of overall center of mass (COMvel), pelvis (COMpelvis_vel) and pulley (CARvel) was then calculated and compared to the velocity measured by MRD (MRDvel) in .5 s intervals 1.5 s before and after CoD. Average velocities from these intervals where then compared using correlational, Bland Altman analysis, coefficient of variation (CV) and statistical parametric mapping (SPM). Mostly excellent correlations were observed and ranged from .93 to 1.00, .53 to 1.00 and .93 to 1.00 for the 3, 6 and 9 kg load conditions respectively. CV values ranged from .3 to 3.2%, .8 to 4.3% and 1.5 to 7.7% for the CARvel, COMpelvis_vel and COMvel comparisons respectively. The biases for CARvel comparisons ranged from -.027 to .05 m/s, -.246 to .128 m/s and -.486 to .082 m/s across all load conditions and time intervals for the CARvel, COMpelvis_vel and COMvel comparisons, respectively. SPM analysis indicated significant differences between MRDvel and COMvel and COMpelvis_vel over short time periods during the CoD, but no difference between MRDvel and CARvel. The velocity measurements obtained by a MRD during a m505 test is valid as low biases, low CV´s and high correlations are observed for the MRDvel to CARvel comparison. As single points of measurement (i.e. laser) has been proven useful to assess other athletic tasks (i.e. sprint running), the single point CARvel comparison is an appropriate comparison for validating MRDvel measurements during the m505 test.